Numerical study of plume patterns in a chemotaxis–diffusion–convection coupling system. (1st March 2016) - Deleuze, Yannick; Chiang, Chen-Yu; Thiriet, Marc; Sheu, Tony W.H.
Highlights: A numerical study investigates chemotaxis–diffusion–convection system. The system presents three states: diffusion, chemotaxis, and convection dominant. Plumes patterns appear in the convection dominant regime. Chemotaxis triggers the formation of plumes from many given initial conditions. Different PDE systems exhibit plume patterns although the physics are different. Abstract: A chemotaxis–diffusion–convection coupling system for describing a form of buoyant convection in which the fluid develops convection cells and plume patterns will be investigated numerically in this study. Based on the two-dimensional convective chemotaxis-fluid model proposed in the literature, we developed an upwind finite element method to investigate the pattern formation and the hydrodynamical stability of the system. The numerical simulations illustrate different predicted physical regimes in the system. In the convective regime, the predicted plumes resemble Bénard instabilities. Our numerical results show how structured layers of bacteria are formed before bacterium rich plumes fall in the fluid. The plumes have a well defined spectrum of wavelengths and have an exponential growth rate, yet their positions can only be predicted in very simple examples. In the chemotactic and diffusive regimes, the effects of chemotaxis are investigated. Our results indicate that the chemotaxis can stabilize the overall system. A time scale analysis has been performed to demonstrate that the critical taxis Rayleigh number for which instabilities set in depends on the chemotaxis head and sensitivity. In addition, the comparison of the differential systems of chemotaxis–diffusion–convection, double diffusive convection, and Rayleigh–Bénard convection establishes a set of evidences that even if the physical mechanisms are different at the same time the PDE systems share similarities.